Inbred rat heredity and sex affect oral oxycodone self-administration and augmented intake in long sessions: correlations with anxiety and novelty-seeking - Burt M. Sharp; Shuangying Leng; Jun Huang; Caroline Jones; Robert W. Williams; Hao Chen (PLoS ONE, 2025)
Oxycodone abuse frequently begins with prescription oral oxycodone, yet vulnerability factors (e.g. sex, genetics) determining abuse are largely undefined. We evaluated genetic vulnerability in a rat model of oral oxycodone self-administration (SA): increasing oxycodone concentration/session (0.025-0.1mg/ml; 1-, 4-, and 16-h) followed by extinction and reinstatement. Active licks and oxycodone intake were greater in females than males during 4-h and 16-h sessions (p < 0.001). Both sexes increased intake between 4-h and 16-h sessions (p < 2e-16), but a subset of strains augmented intake at 16-h (p = 0.0005). Heritability ( h 2 ) of active licks during 4-h sessions at increasing oxycodone dose ranged from 0.30 to 0.53. Under a progressive ratio (PR) schedule, breakpoints were strain-dependent (p < 2e-16). Cued reinstatement was greater in females (p < 0.001). Naive rats were assessed using elevated plus maze (EPM), open field (OF), and novel object interaction (NOI) tests. We correlated these behaviors with 28 parameters of oxycodone SA. Anxiety-defining EPM traits were most associated with SA in both sexes, whereas OF and NOI traits were more associated with SA in males. Sex and heredity are major determinants of motivation to take and seek oxycodone; intake augments dramatically during extended access in specific strains; and anxiety correlates with multiple SA parameters across strains.